Classroom Management Practices of Receiving Teachers Handling Learners with Disabilities - Ditan, Miriam; Turiano, Nodel (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the classroom management practices and challenges of receiving teachers handling learners with disabilities in inclusive classrooms in the Division of Sorsogon for School Year 2025–2026. Anchored on Bronfenbrenner’s Bio-Ecological Systems Theory, Skinner’s Operant Conditioning, Rogers’ Humanistic Theory, the Comprehensive Management Theory for Inclusive Education, and the input-process-output model, the study employed a descriptive quantitative research design. Data were gathered from 30 receiving teachers using a researcher-made survey questionnaire that was reviewed, validated, pilot-tested, and analyzed using percentage, weighted mean, and Likert scale interpretation. Findings showed that most respondents were female, above 40 years old, had 21 years or more of teaching experience, and had attended one to three trainings on classroom management. Classroom management practices were generally rated as always practiced, with building positive relationships ranking highest, followed by promoting learner engagement and providing positive reinforcement. However, the teachers encountered moderate challenges, particularly instructional challenges related to modifying lessons for diverse learning needs and environmental challenges such as large class sizes that limit individualized attention. The study concluded that receiving teachers consistently applied inclusive classroom management practices but still required continued guidance, professional development, resources, and support. A practical guidebook was developed to strengthen teachers’ competencies in managing inclusive classrooms. The study supports SDG 4, SDG 10, SDG 16, and SDG 17 by promoting inclusive education, reducing barriers for learners with disabilities, strengthening institutional support, and encouraging stakeholder collaboration. Its sustainability impact lies in supporting teacher development, evidence-based school planning, inclusive policy implementation, and meaningful learner participation.